Introducing the Anatomy of Resistance Campaigns (ARC) dataset. (May 2022) - Butcher, Charles; Braithwaite, Jessica Maves; Pinckney, Jonathan; Haugseth, Eirin; Bakken, Ingrid Vik; Wishman, Marius Swane
We introduce the Anatomy of Resistance Campaigns (ARC) dataset, which records information on 1, 426 organizations that participated in events of maximalist violent and nonviolent contention in Africa from 1990 to 2015. The ARC dataset contains 17 variables covering organization-level features such as type, age, leadership, goals, and interorganizational alliances. These data facilitate new measurements of key concepts in the study of contentious politics, such as the social and ideological diversity of resistance episodes, in addition to measures of network centralization and fragmentation. The ARC dataset helps resolve existing debates in the field and opens new avenues of inquiry.